Letters from the top: A comparative control group study of CEO letters to stakeholders - Mark Fuller (International Journal of Corporate Social Responsibility (JCSR), 2018)
This paper examines corporate social responsibility (CSR) reporting with a focus on communications from management. It examines letters from the board chair, CEO and/or senior CSR lead to gain a deeper understanding of how firms disclose their past performance and whether firms noted for the CSR reporting disclose their information in meaningfully different ways compared to other firms. Using a comparative analysis between treatment and control groups, we explore whether there is a difference in reporting approaches between a sample of highly regarded CSR reporters vis-à-vis firms recognized for their high profitability. Our findings suggest CSR-recognized firms discuss sustainability issues in greater quantity but without much meaningful difference in quality. We postulate a parabolic relationship between report quality and cost to explain this situation, discussing both the theoretical and the practical implications.
Keywords: 650; Canada; CEO communications; Corporate social responsibility; CSR reporting; Letters to stakeholders; Mandatory reporting; Stakeholder management; Voluntary reporting